Greening economy, graying society - Bretschger, Lucas (Munich, 2015)
"The world economy is affecting ecosystems in a way that puts future living standards at risk. Important issues include global warming, fading resource stocks, scarce water supplies, and decreasing biodiversity. It is broadly ac-accepted that the future of our planet should be one of our major concerns. But when it comes to concrete policies, most clearly those related to climate change, grave difficulties arise. This may come as a surprise. In fact, it should not be surprising. Forward-looking and green policies have always proved to be demanding and controversial. At the global scale, national policy difficulties are only compounded. There is not sufficient consensus across the different countries. World society is not very dynamic in problem solving. Rather, it is graying and inertial, cultivating conservative views and institutions. Economic interests and political perceptions diverge widely across countries. While the potentials offered by green technologies are huge, institutions have not yet adapted to meet the challenges. The political debate lacks sufficient focus; it includes very diverse opinions and notions on admittedly complex issues. It is true that the most prominent sustainability policy, climate policy, combines the most difficult and complex conditions for policy making in a single subject. Correction of a big market failure, international consensus building, long-run planning, major uncertainties, huge equity concerns, and very heterogeneous country interests are ingredients that would bedevil any political decision. On the bright side, concepts such as “green economy” and “sustainable development” have prominently entered the political debate, documenting the rising number of bridges between economy and ecology. Re-source-efficient technologies are increasingly being developed and applied. Yet, while everyone would highly welcome political solutions to the climate problem, accepting their consequences is much less widely embraced. These include significant reductions in natural resource use, especially with fossil fuels. They also entail acknowledging responsibility for past emissions and obligations to other countries and future generations. Consistent sustainability policies require a framework and an institutional setting that has yet to be built and globally implemented. Such a framework would end-able policymakers exploiting the huge potentials for greening the economy. Many scientific and applied contributions on sustainability have al-ready been published. But the majority of the advocated policies have not been implemented; major problems such as global warming have not yet been properly addressed. It appears that sustainability policies are not attracting sufficient political support. By pointing to the profound problems inherent in policy making in this area, this book explains why this is the case. It also provides the elements needed to increase general understanding and to find political consensus. Compared to the much broader scientific contributions on sustainability, some authored by large numbers of international researchers in different disciplines, the present book takes a more modest approach. It draws on selected research results to explain the most important sustainability is-sues from the point of view of economics. The book points at central underlying problems and misperceptions with the aim of increasing ambitions and rationality in political decision making. It reflects the high complexity of reaching sustainable development, which will require the contribution of social sciences involving many different perspectives. The book uses neither formal models nor mathematical equations. These can be found in the underlying original academic works cited in the references. The approach follows that of the famous economist Alfred Mar-shall, who advised using formal analysis until the results were fully de-rived but then to “burn” the mathematics, translate the conclusions into normal language, and illustrate them by “examples that are important in real life.” In following this procedure, this book aims to make the economic approach to sustainability attractive for a broader audience and a useful input to policy making."